Characteristics of Vibrio cholerae O1 CTX+ Strain Isolated from the Temernik River in Rostov-on-Don in 2023 - E. V. Monakhova; V. D. Kruglikov; A. S. Vodop’yanov; Ya. M. Krasnov; S. D. Katyshev; N. A. Sharapova; L. P. Alekseeva; E. A. Men’shikova; V. V. Evdokimova; M. I. Ezhova; A. K. Noskov (Проблемы особо опасных инфекций)
The aim of the work was to determine the pheno- and genotypic features of the aquatic CTX+ strain of Vibrio cholerae isolated in 2023 and a comparative bioinformatic analysis of whole-genome sequencing data.Materials and methods. Whole-genome sequencing was performed on MiSeq (Illumina) and MinIon Oxford Nanopore Technologies (ONT) platforms; hybrid assembly of the whole genome was carried out using the Trycycler algorithm; assembly errors were eliminated by means of the Medaka algorithm and the Pilon program. Dendrogram construction and bioinformatics analysis were carried out with the help of the scipy and Graphviz packages, BioEdit, BLASTN, BLASTP, CARD, ICE Genotyper, and Vector NTI programs. The ability to produce cholera toxin was tested using the GM1ELISA.Results and discussion. The isolated strain was identified as V. cholerae O1 Ogawa, sensitive to most antibiotics. Based on the totality of genetic properties, it was classified as the first genovariant, distinct from the typical El Tor strains only by the presence of ctxB1 gene of classical type instead of ctxB3 of the El Tor type. It has been established that it contains a tandemly duplicated CTX prophage on the small chromosome and a tandem of two copies of RS1 prophage on the large chromosome. Thereat, the rstR gene of the CTX prophage belonged to the classical type, and the RS1 prophage – to the El Tor type. The remaining criteria of epidemic hazard – tcpAelt, rtxA1 and intact VSP-II did not differ from the prototypes. The genome of the strain carries the ICE element VchBan11, which contains the trimethoprim resistance gene dfrA1, and phenotypically the strain is resistant to this antibiotic. Under in vitro conditions, the strain did not produce cholera toxin, as shown by ELISA results. This may be due to the presence of a deletion within the toxR regulatory gene. Strains similar to the 2023 isolate are mainly attributed to the second wave of the seventh pandemic. Currently, they are almost replaced by new genovariants, but occasionally can emerge and even cause diseases. Therefore, their importation into Russian territory potentially pose a threat to public health.